Customer–Company Identification as the Enabler of Customer Voice Behavior: How Does It Happen? - Ran, Yang; Zhou, Hao (Frontiers in Psychology, 2020)
In this study, we define customer voice behavior as a consumer’s extra-role communicative behavior of offering suggestions or opinions to enterprises. We classified customer voice behavior into two dimensions: promotive and prohibitive voices. Furthermore, we explored the relationship between customer–company (C–C) identification and customer voice behavior. From a sample of 394 university students who were customers of food delivery services, the results showed that C–C identification was positively related to both promotive and prohibitive voices while felt responsibility for constructive change (FRCC) played a mediating role between C–C identification and both kinds of customer voice behavior. In addition, we found the moderating effects of self-impact, which could strengthen the impacts of FRCC on customer voice behavior and the mediating effects of FRCC. The theoretical and practical implications of this study are also discussed.